Pengaruh Sosial Ekonomi Terhadap Ketimpangan Pendapatan di Provinsi Bali Tahun 2019–2023 - Rasendriya, Cetta; Kenanga, Annisa Bulan; Wahdah, Firosa Aniqotul; Wulandari, Mayva; Gempati, Abel; Rahajeng, Anggi (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This study aims to determine the effect of IPM, PMA, PDRB, RLS, and population density variables on income distribution inequality in Bali Province. This study employs a quantitative approach, utilizing panel data analysis processed with EViews. The results of this study indicate that HDI has a negative and significant effect, Foreign Direct Investment (FDI) has a positive and significant impact, RLS also shows a positive and significant effect, while GRDP does not show a significant impact on inequality, and Population Density has a positive and significant effect on income distribution inequality in Bali Province. Based on spatial analysis using the hotspot method, the area with high-income distribution inequality based on the Gini Ratio Index data for Bali Province from 2019 to 2023 is Denpasar City.